2002
DOI: 10.1021/jf011200c
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Accumulation in Beef:  Effect of Dietary Selenium and Geographical Area of Animal Origin

Abstract: Selenium (Se) is an essential nutrient with multiple human health benefits; the single most important dietary source of Se is beef. The Se content of beef varies, and cattle fed a high selenium diet may have Se concentrations in beef that are well above average. Such beef is potentially a unique supplemental source of dietary Se. To examine factors affecting Se accumulation in beef, 16 steers (initial wt 374.4 +/- 33.7 kg) were taken from seleniferous or nonseleniferous areas and fed in a 2 x 2 factorial desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 22 publications
4
47
2
Order By: Relevance
“…Hintze et al (2002) showed the similar results to ours, suggesting the limitation of Se accumulation in the muscle of beef steers. They further indicated that the transfer of dietary Se to muscle was inefficient as maximum of 2.6%.…”
Section: Se Deposition In Tissuessupporting
confidence: 89%
See 2 more Smart Citations
“…Hintze et al (2002) showed the similar results to ours, suggesting the limitation of Se accumulation in the muscle of beef steers. They further indicated that the transfer of dietary Se to muscle was inefficient as maximum of 2.6%.…”
Section: Se Deposition In Tissuessupporting
confidence: 89%
“…Even though it has been known to be toxic in dietary Se level from 5 to 20 ppm in swine, resulting in decreased ADG and feed intake (Kim and Mahan, 2001), toxic level of dietary Se for cattle has not been well defined. Hintze et al (2002) reported that a ration containing more than 10 ppm of Se for beef steers did not influence feed intake and showed no any toxic symptoms. One can assume that ruminants might be more tolerable for Se toxicity than monogastrics.…”
Section: Performances and Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kidneys also presented the greatest Se content in other studies, with zebu (Dermauw et al 2014), pigs (Daun and Å kesson 2004) and lambs (Juniper et al 2009). However, Hintze et al (2002), who found the greatest Se concentration in the liver, reported slightly different findings. The kidney is the main site of plasma glutathione peroxidase synthesis and has the greatest Se content per unit of weight (Ducros and Favier 2004).…”
Section: Chemical Composition Of Meatmentioning
confidence: 94%
“…Although geographic differences in the Cu and Se status of beef cattle have been reported Campbell et al 1995;Hintze et al 2002), the effects of differences in water quality and meteorological conditions between grazing pastures have not been examined in western Canada. Sulphate is a frequent contaminant of livestock water sources in the Canadian prairies and north-central regions of the United States.…”
mentioning
confidence: 99%